Molecular detection of Babesia spp. and Ehrlichia spp. in Rhipicephalus sanguineus and dogs from the Zoonoses Control Center of Belém, state of Pará (Research, Society and Development, 2021)
Among the main hemoparasitosis that affect dogs in Brazil and in the world are Babesiosis and Ehrlichiosis, with the Polymerase Chain Reaction (PCR) being the most sensitive and specific test for molecular detection of the respective agents. This work aimed to detect DNA from Ehrlichia spp. and Babesia spp. in samples of Rhipicephalus sanguineus ticks and in the blood of dogs kept in confinement in the Zoonoses Control Center (CCZ) kennel in Belém, Pará State. The collections were carried out from April to June 2019. The evaluated samples were tested for the detection of DNA from Anaplasmataceae and Babesia spp. through Polymerase Chain Reaction (PCR) and Ehrlichia spp. through Semi-Nested PCR. Samples were obtained from 81 dogs from the CCZ, of which 74.1% (60/81) were found to be infested with ticks. Among the blood samples analyzed by PCR, 2.5% (2/81) were positive for Babesia spp., with no detection of the agent in tick samples. On the other hand, 13.6% (11/81) of dogs and 0.96% (1/104) of ticks were positive for Ehrlichia spp. It is concluded that the investigated animals presented a high rate of infestation by Rhipicephalus sanguineus, also observing the occurrence of Babesia spp. and Ehrlichia spp. in dogs from the Zoonoses Control Center in Belém, Pará state.